2009
DOI: 10.1097/nna.0b013e31819894a0
|View full text |Cite
|
Sign up to set email alerts
|

Nurse Leader Mindfulness Meditation Program for Stress Management

Abstract: Results support preliminary effectiveness of a 4-week MMC in reducing self-reported stress symptoms among nursing leaders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
221
1
5

Year Published

2014
2014
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 186 publications
(234 citation statements)
references
References 19 publications
7
221
1
5
Order By: Relevance
“…Studies support the positive benefits of meditation and compassion interventions on a number of health and well-being outcomes including burnout [38][39][40][41][42][43][44][45], and a recent review of mindfulness-based interventions (MBIs) concludes that loving-kindness meditation (LKM) may be the most effective practice for increasing compassion [46]. Unfortunately, the duration of these interventions-often 8 to 15 weeks long-directly conflict with the limited time available to medical practitioners [45,[47][48][49]. There is a need for more effective and efficient interventions that require little time but still have the same positive affective consequences.…”
Section: The Present Studymentioning
confidence: 99%
“…Studies support the positive benefits of meditation and compassion interventions on a number of health and well-being outcomes including burnout [38][39][40][41][42][43][44][45], and a recent review of mindfulness-based interventions (MBIs) concludes that loving-kindness meditation (LKM) may be the most effective practice for increasing compassion [46]. Unfortunately, the duration of these interventions-often 8 to 15 weeks long-directly conflict with the limited time available to medical practitioners [45,[47][48][49]. There is a need for more effective and efficient interventions that require little time but still have the same positive affective consequences.…”
Section: The Present Studymentioning
confidence: 99%
“…Now picture him/her vacuuming them up one at a time until they are all gone inside the vacuum bag. He/she takes out the -experiencing a method to aid reduction in stress and improvement in well-being and resiliency (Richards, Campenni, & Muse-Burke, 2010;Glomb, Duffy, Bono, & Yang, 2011) -enhanced levels of empathic selfawareness, self-compassion and emotional resilience (Shapiro, Brown and Biegel 2007;Krasner et al 2009;Pipe et al 2009;Napoli and Bonifas 2011) SfA, SM bag and drops it into a metal bin. And set light to it or 'magics it away' with the swipe of a wand.…”
Section: Sfa Sm Ee Rs Scamentioning
confidence: 99%
“…Pipe et al 2009;Napoli and Bonifas 2011) -strategic tool to reduce stress because: "An anxious mind cannot exist in a relaxed body." (Dr Edmund Jacobson, 1929) -develop greater focus, build better relationships, and enhance creativity.…”
Section: Reflective Practicementioning
confidence: 99%
“…Randomised controlled trials (RCTs), mostly with wait-list control groups, have found that workplace MBIs decrease perceived stress (Klatt, Buckworth, & Malarkey, 2009;Schenström, Rönnberg, & Bodlund, 2006;Shapiro, Astin, Bishop, & Cordova, 2005;Wolever et al, 2012), anxiety and depression (Pipe et al, 2009), and burnout (Cohen-Katz, Wiley, 2 Capuano, Baker, &Mackenzie, Poulin, & Seidman-Carlson, 2006;Shapiro et al, 2005); and improve life satisfaction (Mackenzie et al, 2006;Shapiro et al, 2005), mood and wellbeing (Pipe et al, 2009;Schenström et al, 2006), sleep quality (Klatt et al, 2009;Wolever et al, 2012), heart rate variability (Wolever et al, 2012), and self-compassion ).…”
Section: Mindfulness In the Workplacementioning
confidence: 99%